Perbedaan Self Efficacy dan Motivasi Berprestasi Ditinjau Dari Gaya Belajar - Rahayu, Nining; ., Suroso (Persona:Jurnal Psikologi Indonesia, 2016)
Research discussed about difference of Self-efficacy between achievementmotivation looked from learning manner with function for to know is there any differenceSelf-efficacy looked from learning style and is there any difference between achievementmotivation looked from learning styles. This research had been done in Phsycologydepartment in Universitas 17 Agustus Surabaya. Method of research is comparasional.Before did the analys of strip varian inter-group was done brochure normalitas andhomogenitas test. Based on the result of one strip varian inter-group was found is resultSelf-efficacy looked from learning styles was gotten that F=0,456 with p=0,635(p>0,05). Its means Self-efficacy to all of subject group was found there was nodifference between learning style by visual, auditori and kinesthetic. Meanwhile result ofachievement motivation looked from with p=0,882 (p>0,05). Its means achievementmotivation for all subject group was not found difference between learning styles byvisual, auditori, and kinesthetic.Keywords : Self-efficacy , Achievement Motivation , Learning Styles